How Pediatric Urology Fellowships in the United States are Funded - Snow, Brent Walter; Wallis, M. Chad (Frontiers in Pediatrics, 2014)
Background: We desired to discover how pediatric urology fellowship positions in the United States were funded. Methods: Approved pediatric urology fellowship directors (25) were contacted by email and asked how the 2 years of fellowship were funded at their institutions. Results: The response rate of the email questions was 100%. The clinical year of the fellowship was 100% hospital-funded in 88% of the 25 fellowships. The second, ABU-required year was 100% hospital-funded in only 44% of the fellowships. Clinical funds generated by pediatric urology faculty provided funding for 24% of the fellows and institutes and grants funded 20% of the fellowship positions for the second year. Thirty two percent of the fellowship positions have supplemental funding through charges generated from the fellow's clinical activities in patient care. Conclusion: All but 3 hospitals fund 100% of the clinical year of pediatric urology fellowship. Sources of funding for the second, ABU-required year vary widely among fellowship programs in the U.S.